Screening for moral injury and comparatively evaluating moral injury measures in relation to mental illness symptomatology and diagnosis. (10th September 2020) - Nieuwsma, Jason A.; Brancu, Mira; Wortmann, Jennifer; Smigelsky, Melissa A.; King, Heather A.; ,; Meador, Keith G.
Abstract: Moral injury merits further study to clarify its identification, prevalence, assessment and intersection with psychosocial and psychiatric problems. The present study investigated the screening potential of the Brief Moral Injury Screen (BMIS) in a sample of post‐9/11 veterans ( N = 315) and comparatively evaluated how this tool, the Moral Injury Events Scale (MIES), and the Moral Injury Questionnaire‐Military Version (MIQ‐M) relate to psychiatric diagnoses and mental illness symptom severity. Those who endorsed failing to prevent or doing something morally wrong had the highest symptomatology scores on measures of posttraumatic stress disorder, depression, suicidality, alcohol abuse and drug abuse, followed by those who reported solely witnessing a moral injury event. Posttraumatic stress disorder and depressive symptoms correlated most strongly with scores on the MIQ‐M; suicidality, alcohol abuse and drug abuse scores correlated most strongly with scores on the BMIS and MIQ‐M. Moral injury, as measured by three scales, was robustly correlated with worse outcomes on various symptom measures. The three scales appear to differentially predict mental illness symptomatology and diagnoses, with the BMIS predicting suicidality and alcohol and drug abuse as well as better than other measures.